Passenger Transport Sustainability in Forty-Six Global Cities: Where Does Istanbul Stand in a Global Transport Sustainability Context - AbuShaban, Bayan; Kenworthy, Jeffrey (IETT, 2013)
Many discussions can be found around sustainability but very few talk about transportation in real concrete terms by examining particular cities using detailed data and benchmarking them properly against each other. The highly summarized work presented in this paper is part of a larger investigation by the authors to document sustainable transport indicators for some of the Middle Eastern and North African (MENA) cities. The research by the authors seeks to benchmark and rank MENA cities against many cities on all continents using standardized variables based on some forty-two transport and land use primary data items. This will show where the MENA cities are situated in sustainable transport terms, and will allow very important policy insights into the future of urban passenger transport in the region. The current paper provides some key comparative data on Istanbul, along with Dubai, which help to position this large Middle Eastern city within this global framework and with one other city in the region.